1998
DOI: 10.1007/s002689900353
|View full text |Cite
|
Sign up to set email alerts
|

Overview on Compression Anastomoses: Biofragmentable Anastomosis Ring Multicenter Prospective Trial of 1666 Anastomoses

Abstract: This study represents a European prospective clinical multicenter trial and was undertaken to evaluate the applicability of the biofragmentable anastomosis ring (BAR) as a routine anastomotic tool in teaching hospitals. The trial results analyzed consisted of 1666 BAR anastomoses performed in 1360 patients from March 1989 to May 1996 in the upper (1042 anastomoses) and lower (624 anastomoses) gastrointestinal (GI) tract. Only patients selected for elective procedures and having previously undergone orthograde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 24 publications
4
33
0
7
Order By: Relevance
“…Thiede and co-workers 209 Clinically indicated by retarded bowel function, fever and localised abdominal fluid.…”
Section: Obertop and Bosschamentioning
confidence: 99%
See 1 more Smart Citation
“…Thiede and co-workers 209 Clinically indicated by retarded bowel function, fever and localised abdominal fluid.…”
Section: Obertop and Bosschamentioning
confidence: 99%
“…Thiede and co-workers 209 conducted a European clinical trial over six centres to evaluate the applicability of a biofragmentable anastomotic ring in upper and lower gastrointestinal surgery in 1360 patients. This was the largest prospective study from the included gastrointestinal literature.…”
Section: Type II (Clinical)mentioning
confidence: 99%
“…Four included experimental studies [107][108][109][110] showed that compression colorectal anastomosis leads to acceptable healing and strength; 6 included RCTs [111][112][113][114][115][116] provide equivalent conclusions, finding no significant differences between hand-sewn and compression colorectal anastomosis. Also, noncomparative clinical cohort studies [142][143][144][145] including up to 1360 patients have reported incidences of AL between 0.7% and 5%. Although few gastrointestinal sur- Abbreviations: see Table 1; ETE, end-to-end; ETS, end-to-side; NIR, not included in the present review (in case a supplemental subgroup was also studied, outside the topic of this review); STE, side-to-end; STS, side-to-side.…”
Section: Hand-sewn Vs Compression Colorectal Anastomosismentioning
confidence: 99%
“…Ischemia, inflammation, and fibrosis due to anastomosis leakage are the factors for anastomotic stenosis [15,16] . No sign of anastomotic stenosis at compression anastomotic site was observed either in upper gastrointestinal contrast radiography early postoperatively or in the endoscopy after a long-term follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients complained of abdominal pain due to dietary. However, Thiede and colleagues conducted a multicenter prospective trial of biofragmentable anastomosis ring and found that a low fiber diet until the evacuation of ring fragments from the bowel could prevent obstruction with no discomfort [16] . The recovery course of 7 patients with a compression anastomosis who had complete intestinal obstruction before surgery, was uneventful and similar to those without complete intestinal obstruction before operation, which might be related to the characteristics of the CAC.…”
Section: Discussionmentioning
confidence: 99%